Surgical outcomes of renal transplant recipients after abdominal surgery not connected with transplantation. A retrospective case-control study. (January 2019) - Lederer, Ann-Kathrin; Haffa, Dominic; Martini, Verena; Huber, Roman; Makowiec, Frank; Fichtner-Feigl, Stefan; Kousoulas, Lampros
Abstract: Background: Due to the increasing number of patients after kidney transplantation, elective and emergency surgery of transplanted patients is becoming a relevant challenge in clinical routine. The current data on complication rate of patients after kidney transplantation, which must undergo another elective or emergency abdominal surgery, is inhomogeneous. Therefore, the aim of our study was to evaluate the outcome of renal transplant patients undergoing abdominal and abdominal wall surgery. Material and methods: We performed an observational study of patients after kidney transplantation undergoing graft-unrelated abdominal surgery between 2005 and 2015. We randomly created a non-transplanted control for a case-matched controlled analysis. Primary endpoint was the comparison of complication rate. Secondary, a risk analysis of all patients was performed and differences in mortality, length of hospital stay and reoperation rates were calculated. Results: Overall 101 kidney transplanted patients were eligible for inclusion. 20 (19.8%) died after graft-unrelated surgery and 60 (59.4%) suffered from postoperative complications. Case-matched analysis could be performed for 84 out of these 101 patients. We found no significant difference in morbidity rate (58.3% vs. 45.2%, p = 0.090). Transplanted patients had, however, a significantly higher mortality (19% vs. 2.4%, p = 0.001), a longer hospital stay (28.2 vs. 16.9 days, p = 0.020) and a higher rate of re-operations (38.1% vs. 20.2%, p = 0.017). . Conclusions: Patients after renal transplantation undergoing graft-unrelated abdominal surgery have a significantly increased mortality risk, are more frequently re-operated and have to stay significantly longer in hospital than non-transplanted patients. Highlights: Kidney transplant recipients are a vulnerable surgical cohort. They have a significantly increased mortality risk after graft-unrelated surgery. They also have a significantly higher rate of reoperations. They have to stay significantly longer in hospital.